The ultrastructure of the pyloric valve region in bees, with considerations of fluid flux in the digestive tract - Serräo, José Eduardo [UNESP]; Da Cruz-Landim, Carminda [UNESP] (My University, 1996)
The pyloric valve region of the gut was studied in adult bees. The pyloric valve is formed by folds of the hindgut epithelium being covered by a thin cuticle (1.7 to 2.0 μm). This cuticle has spine-like structures at the proximal end of the valve while in the distal end they are lacking. The midgut cells located in the transitional point are narrow with short microvilli which decrease in length and disappear in the cells adjacent to the pyloric valve. The transition between mid- and hindguts is marked by flat cells where the cuticle begins to appear. The cells of the pyloric valve are cubical and have a cytoplasm with'clear regions. At their apex there are short microvilli (1.0 μm). The nucleus is located in the middle cell portion and surrounded by vesicular smooth endoplasmic reticulum associated with glycogen deposits. Basal plasmic membrane infoldings, frequently filled with electron-dense material, and some mitochondria are present. The malpighian tubules occur in front of the pyloric valve, contrasting with bee larvae where these insertions are in the hindgut. The results are discussed in relation to the function of this gut region in bees.
Keywords: Bees; Hindgut; Insect; Midgut; Pyloric valve; Ultrastructure